Sustainable banking in Latin American developing countries: Leading to (mutual) prosperity. (4th September 2017) - Forcadell, Francisco Javier; Aracil, Elisa
Abstract : This article examines multinational banks' (MNBs) approaches to corporate social responsibility (CSR) in developing countries' subsidiaries, particularly in Latin America. Building on in‐depth case studies of two MNBs that are based in Europe and market leaders in Latin America, we analyze their CSR motivations and outcomes in host countries. We examine institutional environments by applying the national business system framework, and we suggest missing categories in its financial and educational dimensions. We theorize how institutional necessity determines MNBs' CSR in developing countries. Finally, we examine the CSR outcomes in Latin America, where banks' responsible conduct has led to major improvements in educational levels and financial inclusion. These improvements alleviate poverty and enhance both country's social wellbeing and MNBs' legitimacy, leading to mutual prosperity.